ANALISIS INFORMASI WORD OF MOUTH DALAM PEMBELIAN ONLINE PADA MAHASISWA PROGRAM STUDI MANAJEMEN UBSI - Saniyatul Munawaroh (PT. Hasba Edukasi Mandiri, 2025)
The advancement of information and communication technology has significantly influenced consumer behavior, particularly in online purchasing. Students, as Digital natives, are highly susceptible to the influence of Word of Mouth (WOM), both in personal and electronic forms. This study aims to analyze the impact of WOM information on online purchasing decisions among Management students at Bina Sarana Informatika University (UBSI). The research employed a descriptive quantitative non-statistical approach, with data collected through questionnaires distributed to 99 respondents. The data were analyzed using descriptive statistics, including Frequency, percentage, and average, to illustrate the influence of WOM on purchasing behavior. The findings indicate that WOM significantly affects students’ Purchase decisions, especially when the information comes from Trusted sources such as friends or family. Positive WOM messages enhance Trust and interest in online transactions. These results highlight the importance of implementing credible WOM-based Marketing strategies to improve digital promotional effectiveness, particularly in student markets that are highly active on online platforms.